Penerapan Building Information Modeling (Bim) 5D pada Manajemen Biaya Proyek dalam Dunia Konstruksi - Irika Widiasanti; Mochamad Aldi Wijaya; Serina Anggraini; Olivia Aziza Balqis; Richard Yordan Suryapratama; Bagus Tri Prasetya (Jurnal Talenta Sipil, 2023)
The development of construction in Indonesia today there are still many problems that occur in the implementation of construction. One of them is the problem of project cost budget. Project budget problems are often a failure factor where the cost increase is large and detrimental if the planning process is wrong.  Moreover, errors in project cost management can cause project termination due to lack of funds or cost overrun.  The development and innovation of the construction world today introduces Building Information Modeling (BIM) as a solution to overcome various problems in the construction sector that occur today.  This study used qualitative research methods with descriptive analysis techniques and library research.  The results of this study explain that Building Information Modeling (BIM) can be applied to all fields of construction work, both new projects and renovation projects.